Vertical market structure matters: The case of a horizontal retail merger in the German gasoline market - Sebastian Oschmann (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2025)
This article examines the price effects of gasoline stations following a retail merger in 2022. Using detailed station-level price data from 2020 to 2024, the analysis shows that fuel prices increase at both merging stations and their competitors, but with regional differences. These regional differences cannot be explained by horizontal merger effects. Instead, changes in the vertical market structure play a key role. The divestment of the station network disrupts supply chains, creating demand pressure on local refineries. The findings highlight the importance of vertical relationships in merger assessments.
Keywords: D22; K21; L13; L41; L81; 330; Gasoline Retail Markets; Ex-Post Merger Evaluation; Competition